Studies of adsorptive interaction between Aspergillus niger and the reactive azo dye Procion Blue MX-G - Contato, I. M.; Corso, C. R. (Editora Unesp, 1996)
Aspergillus niger on paramorphogenic form showed to be efficient adsorbent to reactive azo dye Procion Blue MX-G, where it has obtained rates of colour removal above 99% in acid pH, at 120 minutes of equilibrium time. Temperature did not exert expressive influence in the process, and the applicability of Freundlich's, isotherm suggest the occurrence of various molecules layers of adsorbed dye on the substratum surface.
Keywords: Aspergillus niger; adsorption; dye; filamentous fungi